Visualizing Surface Phase Separation in PS-PMMA Polymer Blends at the Nanoscale - Mrđenović, Dušan; Abbott, Daniel; Mougel, Victor; Su, Weitao; Kumar, Naresh; Zenobi, Renato (ACS applied materials & interfaces, 2022)
Phase-separated polymer blend films are an important class of functional materials with numerous technological applications in solar cells, catalysis, and biotechnology. These technologies are underpinned by the precise control of phase separation at the nanometer length-scales, which is highly challenging to visualize using conventional analytical tools. Herein, we introduce tip-enhanced Raman spectroscopy (TERS), in combination with atomic force microscopy (AFM), confocal Raman spectroscopy, and X-ray photoelectron spectroscopy (XPS), as a sensitive nanoanalytical method to determine lateral and vertical phase-separation in polystyrene (PS)-poly(methyl methacrylate) (PMMA) polymer blend films. Correlative topographical, molecular, and elemental information reveals a vertical phase separation of the polymers within the top ca. 20 nm of the blend surface in addition to the lateral phase separation in the bulk. Furthermore, complementary TERS and XPS measurements reveal the presence of PMMA within 9.2 nm of the surface and PS at the subsurface of the polymer blend. This fundamental work establishes TERS as a powerful analytical tool for surface characterization of this important class of polymers at nanometer length scales.